Evaluasi Diri pada Manajemen Pergudangan terhadap Peningkatan Kinerja Karyawan PT. Pulau Seroja Jaya Banjarmasin - Kamsariaty, Kamsariaty; Tazril, Harmuzan (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2024)
PT.Pulau Seroja Jaya Banjarmasin, this company is a logistics service provider that provides warehousing services. Logistics services consist of warehousing, distribution and transportation services. Operationally, warehousing is a series of management activities in logistics storage starting from receiving, recording, entering, storing, organizing, bookkeeping, maintaining, issuing, and distributing activities to warehouse management accountability activities (making reports) with the aim of supporting the continuity of work units, as well as the effectiveness and efficiency of the organization as a whole. The research method used was descriptive qualitative research. Data processing techniques in the form of observation, interviews, documentation and library literature.The conclusions in this study include Assessment of self-evaluation and performance of warehouse employees is the activity of managers or superiors to evaluate the behavior of employee performance and determine subsequent policies, Performance appraisal is included in human resources, comparative human resources are the key to company success. With the performance appraisal of employees, employees will always try to do as much as possible in every activity given by the company or leader and managers are also easy to carry out company activities in the field of raising positions from employees or seeing employee performance that is not optimal. In addition, another goal of the company to conduct self-evaluation and performance appraisal of warehouse employees is the company's efforts in fostering human resources to improve the performance and competence of the employees concerned. Performance Appraisal is not a punishment but a form of leadership attention to employees.Suggestions for PT Pulau Seroja Jaya Banjarmasin In order for the employees of the warehousing section to further improve their ability to work, both in terms of increasing the quality, quantity and time in carrying out the work assigned. Then employees can take part in training on warehousing management to increase employee expertise and skills in doing their jobs.